MENINGKATKAN KESEJAHTERAAN KEPALA KELUARGA PEREMPUAN MELALUI MODAL USAHA DI BEKASI - Nazila Aryanti; Fayya Bariyyatassyifa; Qonita Naila Salsabila (Fisip UIN Sunan Gunung Djati Bandung, 2024)
Poverty has become a common problem that is being faced by developing countries in particular. Poverty is caused by several factors such as lack of employment opportunities, insufficient salaries to meet living needs and low quality of life of the community. Women who are the backbone of the family are the ones who feel the most impact. Therefore, this empowerment program is focused on helping to improve the economic welfare of female heads of families by providing business capital in the Bekasi area, West Java. The method implemented in this empowerment program is PAR (Participatory Action Research), which can help students to be actively involved in the empowerment process from finding partners, stakeholders, designing programs, etc. The results of this empowerment program showed that although Mrs. Asih had experienced a decrease in income because she had not sold at her stall for a long time, Mrs. Asih earned an income that could meet her daily needs.